2021
DOI: 10.33369/j.akuntansi.11.3.271-284
|View full text |Cite
|
Sign up to set email alerts
|

Penghindaran Pajak: Analisis Perbandingan Antara Sektor (Periode 2017-2019)

Abstract: Setiap sektor mempunyai kontribusi terhadap penerimaan negara berupa pajak. Beberapa sektor mempunyai peraturan perpajakan yang spesifik dan berbeda dibanding dengan sektor lainnya. Hal tersebut membuat adanya perbedaan startegi dan manajemen pajak pada sektor tersebut. Aktifitas penghindaran pajak dapat mengurangi pendapatan negara dari pajak. Penelitian ini adalah menguji apakah terdapat perbedaan penghindaran pajak yang dilakukan oleh setiap sektor yang ada di Bursa Efek Indonesia. Metode purposive sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The population used in this research is the manufacturing companies sector Basic Industries and Chemical and Consumer Goods Industry listed in the Indonesia stock exchange (IDX) for pre-covid-19 period from 2014 to 2018 using purposive sampling method. This is important to search because it is found that tax avoidance from these sectors is higher than other like property, real estate, and building construction sector (Widyasari et al, 2021). sampling on manufacturing companies is based on the following reasons: manufacturing company has a contribution to national's tax revenue besides the other sector of industries, basic industry and chemical and consumer goods industry are the sectors that have basic elements that are often used in daily activities and manufacturing company several times has included in the list of audits that become the focus of Directorate General of Taxation (Dharma & Noviari, 2017).…”
Section: Data and Samplingmentioning
confidence: 99%
“…The population used in this research is the manufacturing companies sector Basic Industries and Chemical and Consumer Goods Industry listed in the Indonesia stock exchange (IDX) for pre-covid-19 period from 2014 to 2018 using purposive sampling method. This is important to search because it is found that tax avoidance from these sectors is higher than other like property, real estate, and building construction sector (Widyasari et al, 2021). sampling on manufacturing companies is based on the following reasons: manufacturing company has a contribution to national's tax revenue besides the other sector of industries, basic industry and chemical and consumer goods industry are the sectors that have basic elements that are often used in daily activities and manufacturing company several times has included in the list of audits that become the focus of Directorate General of Taxation (Dharma & Noviari, 2017).…”
Section: Data and Samplingmentioning
confidence: 99%